Kunstnu. - LUCIE-SMITH, E. (Bussum : Thoth, 1995)
Abate, Alberto ; Ackling, Roger ; Adu, Osi ; African (Cookthorne, Robert) ; Ahearn, John ; Aksel, Erdag ; Alexander, Peter ; Amaral, Jim ; de Amaral, Olga ; Andre, Carl ; de Andrea, John ; Andrejevic, Milet ; Antrim, Craig ; Aponovich, James ; Appel, Karel ; Applebroog, Ida ; Arakawa, Shusaku ; Arango, Ramiro ; Arcevia, Bruno d' ; Arienzo, Miguel d' ; Arita, Akira ; Armajani, Siah ; Arman ; Arneson, Robert ; Arnoldi, Charles ; Art & Language ; Artschwager, Richard ; Atkinson, Conrad ; Auerbach, Frank ; Azaceta, Luis Cruz ; Bacon, Francis ; Baechler, Donald ; Bailey, William ; Baldessari, John ; Barry, Judith ; Bartlett, Jennifer ; Barton, Glenys ; Baselitz, Georg ; Basquiat, Jean-Michel ; Bates, David ; Bawa, Manjit ; Baykam, Bedri ; Beal, Jack ; Bearden, Romare ; Beauchamp, Robert ; Beckman, William ; Bell, Charles ; Bellany, John ; Bennett, Gordon ; Benton, Fletcher ; Berkhout, Rudie ; Berlant, Tony ; Berni, Antonio ; Berredo, Hilton ; Berrocal, Miguel ; Beuys, Joseph ; Bevan, Tony ; Bhattacharjee, Bikash ; Bickerton, Ashley ; Birmelin, Robert ; Birnbaum, Dara ; Bleckner, Ross ; Bloom, Barbara ; Boelatov, Eric ; Alighiero e Boetti ; Bonevardi, Marcello ; Bong Tae-Kim ; Booth, Chris ; Borges, Jacobo ; Borofsky, Jonathan ; Boshier, Derek ; Boskovich, John ; Botero, Fernando ; Bourgeois, Douglas ; Bourgeois, Louise ; Boyce, Sonia ; Boyd, Arthur ; Braun-Vega, Herman ; Brisley, Stuart ; Broodthaers, Marcel ; Brown, Roger ; van Bruggen, Coosje ; Buren, Daniel ; Burgin, Victor ; Burton, Scott ; Bustamante, Jean-Marc ; Butterfield, Deborah ; Caballero, Luis ; Campbell, Steven ; Cappuccio, Antonella ; Cardenas, Juan ; Caro, Anthony ; Castle, Wendell ; Ceccobelli, Bruno ; Celis, Pérez ; Celmins, Vija ; Chadwick, Lynn ; Chamberlain, John ; Chandra, Avinash ; etc.
boek